2006
DOI: 10.1021/ja057254a
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Cell Imaging and Photothermal Therapy in the Near-Infrared Region by Using Gold Nanorods

Abstract: Due to strong electric fields at the surface, the absorption and scattering of electromagnetic radiation by noble metal nanoparticles are strongly enhanced. These unique properties provide the potential of designing novel optically active reagents for simultaneous molecular imaging and photothermal cancer therapy. It is desirable to use agents that are active in the near-infrared (NIR) region of the radiation spectrum to minimize the light extinction by intrinsic chromophores in native tissue. Gold nanorods wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

32
4,271
5
32

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 5,088 publications
(4,340 citation statements)
references
References 36 publications
32
4,271
5
32
Order By: Relevance
“…26,27 More recently, Huang et al provided an in vitro demonstration of gold nanorods conjugated to anti-EGFR antibodies as novel contrast agents for both NIR cell imaging and photothermal cancer therapy. 28 The effectiveness of nanoparticles as biomedical imaging contrast and therapeutic agents depends on their optical properties. For instance, a high-scattering cross-section is essential for cell imaging applications based on light-scattering microscopy.…”
Section: Introductionmentioning
confidence: 99%
“…26,27 More recently, Huang et al provided an in vitro demonstration of gold nanorods conjugated to anti-EGFR antibodies as novel contrast agents for both NIR cell imaging and photothermal cancer therapy. 28 The effectiveness of nanoparticles as biomedical imaging contrast and therapeutic agents depends on their optical properties. For instance, a high-scattering cross-section is essential for cell imaging applications based on light-scattering microscopy.…”
Section: Introductionmentioning
confidence: 99%
“…13 The formation of more complex metal nanostructures, such as metallodielectric gold nanoshells 14 and gold nanocages, 15 shifts the LSPR resonance to the near-infrared (NIR) enabling significant diagnostic and therapeutic biomedical applications. 16,17 Here we describe the synthesis and optical properties of branched star-shaped gold nanoparticles which incorporate polarization-dependent scattering with multiple spectral peaks and strong dielectric sensitivity into a single structure.Due to the symmetric face-centered cubic lattice of gold nanoparticles, the formation of anisotropic structures requires a selective capping agent during growth. For example, roomtemperature synthesis of gold nanorods with 97% yield has recently been demonstrated by seed-mediated growth directed by the surfactant cetyltrimethylammonium bromide (CTAB), 18,19 and the process can be scaled up to 100 mL batches.…”
mentioning
confidence: 99%
“…Using nanoshells with a 110 nm silica core diameter and a 10 nm Au shell, the authors reported significant reduction of human breast carcinoma epithelial cells (SK-Br-3) both in vitro and in a mouse model. Since then there have been many accounts of laser initiated hyperthermia using a variety of nanoparticles with solid Au spheres, cubes, stars, shells and rods all demonstrating successful results in photothermal applications [119,167,189,197,[206][207][208][209][210][211][212].…”
Section: Photothermal Ablation (Pta) Therapymentioning
confidence: 99%